2020
DOI: 10.15252/emmm.202013533
|View full text |Cite
|
Sign up to set email alerts
|

The riddle of the Sphinx: why sphingosine‐1‐phosphate may help define molecular mechanisms underlying risk stratification for serious COVID‐19 infections

Abstract: The sphingosine-1-phosphate (S1P) is a lysophospholipid signaling molecule with important functions in many physiological and pathological conditions, including viral infection. In this issue of EMBO Molecular Medicine, Marfia et al present a risk stratification based on S1P serum level as a novel prognostic indicator for COVID-19 severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…S1P, which is a signaling molecule, exerts multiple functions, including regulating the cytokine storm through its specific G protein-coupled receptors. S1P was significantly reduced in the peripheral blood of patients with COVID-19, and lower S1P meant worse prognosis [15,22,26]. In this study, S1P was found to have the lowest level at the time of discharge and gradually increased during the recovery process.…”
Section: Key Metabolic and Microbial Biomarkers Promote The Recoverymentioning
confidence: 46%
“…S1P, which is a signaling molecule, exerts multiple functions, including regulating the cytokine storm through its specific G protein-coupled receptors. S1P was significantly reduced in the peripheral blood of patients with COVID-19, and lower S1P meant worse prognosis [15,22,26]. In this study, S1P was found to have the lowest level at the time of discharge and gradually increased during the recovery process.…”
Section: Key Metabolic and Microbial Biomarkers Promote The Recoverymentioning
confidence: 46%
“…Recent studies indicate that levels of S1P in patient serum change during the course of COVID-19 with lower circulating S1P observed in patients with a more severe clinical course (Marfia et al, 2021;Rosen and Oldstone, 2021). In view of this, it was suggested that S1P could be a prognostic marker to define the outcome of COVID-19.…”
Section: S1p As a Prognostic Marker For Sars-cov-2mentioning
confidence: 99%
“… 212 S1P/S1PR pathway is also closely associated with neuroinflammation, vascular disease, and other complications of COVID‐19. 213 , 214 S1P can act as an intracellular second messenger and receptor ligand, and regulation of innate and adaptive immunity is mediated primarily through binding to specific GTP‐binding protein‐coupled receptors (S1PR1‐5). 209 , 215 These S1PRs determine multiple responses and are discrepantly expressed in different tissues.…”
Section: Inflammatory Pathways In Covid‐19mentioning
confidence: 99%
“…S1P was considered as a new predictor of clinical severity associated with COVID‐19 212 . S1P/S1PR pathway is also closely associated with neuroinflammation, vascular disease, and other complications of COVID‐19 213,214 . S1P can act as an intracellular second messenger and receptor ligand, and regulation of innate and adaptive immunity is mediated primarily through binding to specific GTP‐binding protein‐coupled receptors (S1PR1‐5) 209,215 .…”
Section: Inflammatory Pathways In Covid‐19mentioning
confidence: 99%